Affective Features Underlying Depression in Addiction: Understanding What It Feels Like - Flores Mosri, Daniela (Frontiers in Psychology, 2019)
Addiction poses a complex challenge in spite of all the progress made at understanding and treating it. A multidisciplinary approach is needed and this paper attempts to integrate relevant neurobiological and subjective data under a common denominator described as a “silent” type of depression. It is called “silent” because it remains a latent syndrome due to two main reasons. The first one relates to the natural use of defenses against a predominant affect of chronic subjective pain that arises from an ambivalent type of separation distress that compromises opioid regulation (PANIC system). Furthermore, it provokes a neurochemical cascade that impacts several neuromodulatory systems. The second reason is that such chronic subjective pain usually exhausts the natural defensive system, frequently leading the person to look for other resources such as the neurochemical manipulation of psychic pain. Thus, both the use of defenses and of psychotoxic drugs make the underlying depression hard to assess, even to the very person suffering from it. The causes, course and treatment of this type of affective configuration are discussed in this paper as an attempt to explain some of the difficulties so far encountered and to contribute to potential alternative lines of treatment.